Aggregated combinatorial reliability model for non-repairable parallel phased-mission systems. (August 2018) - Zhai, Qingqing; Xing, Liudong; Peng, Rui; Yang, Jun
Highlights: Reliability modeling of phased-mission systems with many phases is studied. An aggregated BDD is proposed to simultaneously model all the phases. The scale of the aggregated BDD is independent of the number of phases. Reliability evaluation of PMSs based on aggregated BDD is developed. Abstract: Phased-mission systems (PMSs) are common in many real-world applications. A PMS has to accomplish a mission with multiple phases with varied requirements on system operation and demand. Reliability evaluation of PMSs is more challenging than single-phased systems due to dynamics in system configuration (or structure function) and component behavior, as well as inherent inter-phase dependence. Though many efforts have been dedicated to the PMS reliability analysis, it is still difficult to evaluate the reliability of a large-scale PMS with many phases. In this paper, we make original contributions by proposing a new combinatorial model, named aggregated binary decision diagram (ABDD) for reliability analysis of non-repairable parallel PMSs subject to dynamic demand requirements. The proposed approach constructs a single ABDD model considering failure combinations in all phases simultaneously, enabling efficient analysis of PMSs with many phases. The approach is also extended to address the effects of fault level coverage. Examples of PMSs with different scales are analyzed to demonstrate application and efficiency of the proposed ABDD-based approach.